Effect of Sowing Date on the Performance of Two Sesame (Sesamum indicum L.) Cultivars under Irrigation at Kennana, Sudan (University of Khartoum Journal of Agricultural Sciences, 2025)
The effect of five sowing dates (15/6, 1/7, 15/7, 1/8 and 15/8)on phonology and yield of two sesame cultivars grown under irrigationwas studied at Kennana Sugarcane Research Farm during 2001and 2002seasons. The results showed that plants sown earlier (June sowing)significantly took more days to 50% flowering and physiological maturitythan the late-sown plants (August sowing) in both seasons. In contrast, nosignificant difference between the cultivars was recorded in number ofdays to 50% flowering. Seed yield and yield components weresignificantly affected by sowing date. Early-sown plants (mid June) gave100% and 75% higher seed yield than the late-sown plants (mid August)in the first and the second season, respectively. The higher seed yield ofthe early-sown plants was associated with high number of capsules,number of seeds per capsule and seed weight. The cultivar Promosignificantly exceeded Khidir in seed yield, capsule setting and in numberof seeds per capsule particularly in the first season. It can be concludedthat the optimum sowing date for sesame under irrigation at Kennana ismid June, and that the cultivar Promo is more promising than the cultivarKhidir
Keywords: Sesame; sowing date; irrigation